Sistem Informasi Laundry sesuai Syar’at Islam Berbasis Web - Amna, Amna; Ratna Dewi; Putri Salsabila; Rahmadi Asri; Lenawati Asry (UNIVERSITAS STEKOM, 2023)
A well-prepared abstract enables the reader to Information Technology is very developed in the business world, both small businesses and medium to upper enterprises have all used technology, with the existence of technology the community can change the way of thinking to follow developments. With the existence of computer information systems can provide information quickly and accurately.there are some consumers in the field who hesitate to laundry their clothes because there is still a thought whether washing has been sharia or not, with there is information technology.